SENSORY EVALUATION AND SURVIVAL OF PROBIOTICS IN MODIFIED BANANA FLOUR YOGHURT DURING STORAGE [Evaluasi Sensori dan Sintasan Probiotik dalam Yoghurt Tepung Pisang Modifikasi selama Penyimpanan] - Betty Sri Laksmi Suryaatmadja Jenie; Muhamad Yusuf Saputra; . Widaningrum (Jurnal Teknologi dan Industri Pangan, 2013)
Modified uli banana flour (MUBF) rich in resistant starch as prebiotic source was formulated in yoghurt making to substitute skim milk at various concentrations i.e. 40, 50, 60, and 70%. Yoghurts were prepared using Lactobacillus bulgaricus and Streptococcus thermophilus as the starter cultures. The objective of this study was to determine the maximum MUBF concentration to produce yoghurt with good sensory quality and good number of surviving probiotics (Bifidobacterium bifidum and Lactobacillus plantarum BSL) in non-pasteurized and pasteurized (90ºC, 30 minutes) MUBF yoghurt during 4 week of storage at 10ºC. Hedonic rating and ranking test on yoghurt attributes (aroma, taste, consistency, texture, color and overall preference) performed by 35 untrained panelists showed that yoghurt produced with 70% MUBF substitution achieved good preferences in all of the attributes ranging from neutral to like. The pH value of the product decreased with increase in MUBF concentration. In addition, titratable acidity (TA), expressed as % lactic acid, increased. Survival of both probiotics in 70% MUBF yoghurt either in the pasteurized synbiotic or non-pasteurized yoghurts were still relatively high at week 4. The yoghurt still contains 108CFU/ml of lactic acid bacteria, although this was a log decrease from the initial count. Therefore, the MUBF yoghurt was promising as synbiotic yoghurt based on the probiotic counts throughout 4 week of storage, which was higher than the minimum level recommended (106 CFU/ml) to provide the beneficial effect.